2014
DOI: 10.1371/journal.pone.0101818
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Silybin Nanoparticles Educe Efficient Control in Experimental Diabetes

Abstract: Silybin, is one imminent therapeutic for drug induced hepatotoxicity, human prostrate adenocarcinoma and other degenerative organ diseases. Recent evidences suggest that silybin influences gluconeogenesis pathways favorably and is beneficial in the treatment of type 1 and type 2 diabetes. The compound however is constrained due to solubility (0.4 mg/mL) and bioavailabilty limitations. Appropriate nanoparticle design for silybin in biocompatible polymers was thus proposed as a probable solution for therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Also, the levels of HbA1c, insulin, cholesterol, triglyceride, liver enzyme levels, and antioxidant status parameters (including superoxide dismutase (SOD), catalase, and glutathion (GSH)) are close to that of healthy controls when compared with animals treated with conventional silibin. In another study, silimarin succeeded in restoring SOD, glutathione peroxidase (GSHPx), and catalase (CAT) values to approximately those of the control group, providing another strong indication that it is a free-radical scavenger, able to protect the pancreas from further alloxan-induced damage [19,20].…”
Section: Animal In Vivo Studiesmentioning
confidence: 97%
“…Also, the levels of HbA1c, insulin, cholesterol, triglyceride, liver enzyme levels, and antioxidant status parameters (including superoxide dismutase (SOD), catalase, and glutathion (GSH)) are close to that of healthy controls when compared with animals treated with conventional silibin. In another study, silimarin succeeded in restoring SOD, glutathione peroxidase (GSHPx), and catalase (CAT) values to approximately those of the control group, providing another strong indication that it is a free-radical scavenger, able to protect the pancreas from further alloxan-induced damage [19,20].…”
Section: Animal In Vivo Studiesmentioning
confidence: 97%
“…It was found that engineered nanoparticles of silybin can normalize blood glucose and serum insulin levels and can significantly reduce glycosylate hemoglobin (HbA 1c ) level and restore liver glycogen content and exhibit normoglycemic condition during 28‐day treatment in streptozotocin induced diabetic rats. The suggested mechanism of antidiabetic effect of silybin could be an antioxidant defense mechanism that can help in regeneration of beta cells (Das et al, ). Another study evaluating the therapeutic effect of different forms of silybin in hypertriglyceridemic rats showed micronized form possessed the most significant reductions in glucose and insulin levels.…”
Section: Effect On Diabetesmentioning
confidence: 99%
“…(B) Computer-rendered images of composite scaffold showing (a) a porous structure of the scaffold in 3D and (b) a zoomed section to better display the pore network (1 mm across) (adopted from Hatton et al, 2019). (C) Histopathology examination of pancreas sections-(a) normal pancreas, (b) diabetic pancreas, (c) silybin (Sb)-treated pancreas, (d) Sb nanoparticle-treated pancreas (adopted from Das et al, 2014).…”
Section: Cardiac Tementioning
confidence: 99%